Examination of Grade 5th Turkish Textbook in terms of Picture-Text Relationship - Demirel, Şener; Kökçü, Yelda; Eser, Rabia Sena Akbaba (My University, 2018)
Textbooks are one of the tools that contribute to the learning and trainingof learners. Textbooks with an easy-to-access guide should be prepared ina way that fits student-level and supports student development in terms ofform and content. Textbooks designed in accordance with the level of thestudents are also attracted by students. The preparation of these books bytaking into consideration the qualifications required for the tools used ineducation helps to achieve the educational objectives. One of theeducational features in the textbooks is the pictures accompanying thetexts. In this research, it is aimed to reveal the relation between the picturesin the 5th grade Turkish textbook published by the Ministry of NationalEducation in the academic year of 2017-2018 with the texts. In thequalitative research, the document analysis technique will be used. Thenumber of pictures used in the book, the way the pictures and texts arerelated, the colors used, and the color of the children, etc. examined in thisstudy. The findings obtained as a result of the examination presented witha descriptive analysis table. As a result, in the eight texts examined, it wasseen that the pictures in combination with the text were selected inaccordance with the contents of the texts. Various suggestions have beendeveloped for the missing parts in terms of image-text relation.
Keywords: Eğitim; Eğitim Araştırmaları